Myocardial tissue characterization and mortality in transcatheter aortic valve replacement. (25th November 2020) - Nitsche, C; Kammerlander, A.K; Koschutnik, M.K; Dona, C.D; Sinnhuber, L.S; Eidenberger, A.E; Forutan, N.F; Andreas, M.A; Hengstenberg, C.H; Mascherbauer, J.M
Abstract: Background: Cardiac decompensation in severe aortic stenosis involves accumulation of myocardial extracellular matrix and congestion, which can be objectively quantified by cardiac magnetic resonance (CMR) and bioelectrical impedance spectroscopy (BIS). The aim of this study was to determine whether the extent of extracellular matrix pre-intervention correlates with congestion and is associated with adverse outcomes. Methods: Consecutive patients scheduled for transcatheter aortic valve replacement (TAVR) underwent assessment of volume status using BIS, and CMR, and were prospectively followed. CMR included T1 mapping and extracellular volume (ECV) quantification for the assessement of diffuse myocardial tissue alterations and T2 mapping (n=100) for the assessment of myocardial edema. The combination of all-cause death and heart failure (HF) hospitalization was selected as primary study endpoint. Results: 180 patients (80.6±7.2 y/o, 48.9% female) with valid BIS and CMR data were included. ECV levels≥median was linked to worse ventricular function, more severe pulmonary hypertension and mitral/tricuspid regurgitation (p for all<0.05). Fluid levels significantly correlated with ECV (r=0.403, p<0.001) and T2 (r=0.378, p=0.015), but not T1 relaxation times (p>0.05). Moreover, fluid levels were independently associated with CMR-ECV by multivariate linear regression analysis (p<0.001), alongside with body mass index, left ventricular ejection fraction and hematocrit (p for all<0.05). In total, 22.9% (39/170) had experienced an event (22 deaths, 17 heart failure) 13.4±7.5 months following TAVR. ECV levels≥median of 27.0% were significantly associated with the combined endpoint by Kaplan Meier estimates (log rank, p<0.001, Figure 1), but also with HF hospitalization (p<0.001) and death (p=0.020), when analyzed separately. Quantitively, every 1% increase in ECV increased event hazard by 11% [hazard ratio 1.111, 95% confidence interval 1.030–1.198, p=0.007]. After multivariate adjustment for important clinical, laboratory and CMR parameters, ECV≥median remained independently associated with outcome (p=0.045), alongside with serum albumin (p<0.001) and body fluid levels (p=0.015) by Cox regression analysis. Conclusions: Cardiac decompensation in AS involves myocardial ECV expansion and body fluid accumulation. Fluid accumulation seems to impact the amount of ECV, and both parameters are independently associated with adverse outcomes following TAVR. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Österreichische Kardiologische Gesellschaft